Cerebral Small Vessel Disease Burden Is Associated with Motor Performance of Lower and Upper Extremities in Community-Dwelling Populations - Su, Ning; Zhai, Fei-Fei; Zhou, Li-Xin; Ni, Jun; Yao, Ming; Li, Ming-Li; Jin, Zheng-Yu; Gong, Gao-Lang; Zhang, Shu-Yang; Cui, Li-Ying; Tian, Feng; Zhu, Yi-Cheng (Frontiers in Aging Neuroscience, 2017)
Objective: To investigate the correlation between cerebral small vessel disease (CSVD) burden and motor performance of lower and upper extremities in community-dwelling populations. Methods: We performed a cross-sectional analysis on 770 participants enrolled in the Shunyi study, which is a population-based cohort study. CSVD burden, including white matter hyperintensities (WMH), lacunes, microbleeds (CMBs), perivascular spaces (PVS), and brain atrophy were measured using 3T magnetic resonance imaging. All participants underwent quantitative motor assessment of lower and upper extremities, which included 3-m walking speed, 5-repeat chair-stand time, 10-repeat pronation-supination time, and 10-repeat finger-tapping time. Data on demographic characteristics, vascular risk factors, and cognitive functions were collected. General linear model analysis was performed to identify potential correlations between motor performance measures and imaging markers of CSVD after controlling for confounding factors. Results: For motor performance of the lower extremities, WMH was negatively associated with gait speed (standardized β = -0.092, p = 0.022) and positively associated with chair-stand time (standardized β = 0.153, p < 0.0001, surviving FDR correction). For motor performance of the upper extremities, pronation-supination time was positively associated with WMH (standardized β = 0.155, p < 0.0001, surviving FDR correction) and negatively with brain parenchymal fraction (BPF; standardized β = -0.125, p = 0.011, surviving FDR correction). Only BPF was found to be negatively associated with finger-tapping time (standardized β = - 0.123, p = 0.012). However, lacunes, CMBs, or PVS were not found to be associated with motor performance of lower or upper extremities in multivariable analysis. Conclusions: Our findings suggest that cerebral microstructural changes related to CSVD may affect motor performance of both lower and upper extremities. WMH and brain atrophy are most strongly associated with motor function deterioration in community-dwelling populations.